The outcome of infliximab dose doubling in 157 patients with ulcerative colitis after loss of response to infliximab. Issue 10 (10th September 2015) - Dumitrescu, G.; Amiot, A.; Seksik, P.; Baudry, C.; Stefanescu, C.; Gagniere, C.; Allez, M.; Cosnes, J.; Bouhnik, Y.
Summary Background Optimising infliximab therapy is recommended in inflammatory bowel disease (IBD) patients who lose response to infliximab; however, there are no data on the outcome of ulcerative colitis (UC) patients after doubling the dose. Aim To determine the efficacy and safety of infliximab dose doubling in UC patients with a loss of response to infliximab. Methods From January 2006 to May 2013, we retrospectively reviewed the outcome of the consecutive UC patients who were treated with infliximab dose doubling (10 mg/kg) for loss of response in four French academic centres. The clinical response and remission were assessed. A composite event‐free survival analysis was performed using the log‐rank test and the Cox model. Results One hundred and fifty‐seven patients [84 males; median age 37. 6 (IQR 28.2–49.4) years] were included. The median follow‐up after infliximab dose doubling was 1.8 (1.0–3.1) years. At weeks 8 and 24, 55% and 43% of the patients achieved a clinical response respectively. The probabilities of the event‐free survival were 71%, 61% and 55% at 6 months, 1 year and 2 years respectively. In the multivariate analysis, the predictors of infliximab dose doubling failure were the absence of the introduction of an immunomodulator concomitantly to dose doubling, a partial Ulcerative Colitis Disease Activity Index >6, a C‐reactive protein level >10 mg/L, a leucocyte count >8000/mm3 and a haemoglobin level <12.5 g/dL. Adverse events were reported in 12 patients (8%). Conclusions Infliximab dose doubling led to short‐ and long‐term event‐free survival in UC patients, who had a loss of response to infliximab, in greater than 50% of the cases. The benefits of such a strategy were significantly improved by adding a concomitant immunomodulator.